Pengaruh Altman Z-Score Terhadap Realized Return Perusahaan Terbuka di Indonesia - Andre Reinaldi; Devia Alvionita; Vebby Tjakranegara; Yane Chandera; Rathria Arrina Rachman (Studi Akuntansi dan Keuangan Indonesia, 2020)
This study aims to examine whether there is a relationship between Altman Z-Score (financial distress predictor) and realized return on company’s stock, and how much the influence of Altman Z-Score on the realized stock returns. One way to find out the company's financial condition is using the Altman Z"-score Modification method (Altman, 2002) which is applied in this research. The sample in this study is public companies that are listed on the Indonesia Stock Exchange during the period 2013-2017. This study finds that the company's Altman Z-Score has a positive effect on the realized stock market returns, which means that when a company approaches the condition of is getting closer to financial distress, the realized return on its shares is lower. This study is in line with previous research by Campbell et al. (2008), Dichev (1998), and Griffin and Lemmon (2002). This research is useful for investors for determining their investment strategy and for companies’ management for monitoring and maintaining the company's good financial condition. Keywords: Altman Z-Score, financial distress, stock market return, Indonesia https://doi.org/10.21632/saki.2.2.251-276